Kajian Yuridis Wanprestasi Dalam Pelaksanaan Perjanjian Pinjam Meminjam Antara Kreditur Dan Debitur : Studi Kasus Putusan Nomor 71/PDT.G/2023/PN KPG - Tenci Lioni Andini Kese; Darius Mauritsius; Husni Kusuma Dinata (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to find out and analyze the study of the default judiciary in the implementation of the lending agreement between creditors and debtors based on case number 71/PDT. G/2023/PN KPG. This research is a normative law research that uses primary legal materials and secondary legal materials. The approach methods used in this study include the Case Approach, the Conceptual Approach, and the Statute Approach. The researcher performs this technique by collecting source materials and then doing so by reading, studying, analyzing, recording and interpreting points related to the problems or legal issues raised by the researcher. The results of this study show (1) The form of default committed by the defendants or debtors as contained in decision number 71/Pdt. G/2023/PN. Kpg The form of default committed by the debtors and/or the defendants as the judgment in question is a form of default "carrying out the achievement but not as it should" (2) The legal consequences that must be borne by the defendants are having to pay compensation that is many times the amount of the previous loan, namely from Rp. 350,000,000,- (three hundred and fifty million) to Rp. 612,847,022,- (six hundred and twelve million eight hundred and forty-seven twenty-two rupiah) and must pay the cost of the case and must give up the bail if seven days after the legally effective judgment remains to be confiscated and the factors that cause the perpetrators of the default can be categorized into internal factors and external factors.